VIBRATION ACCELERATION AT HIGH FREQUENCY AT 1 kHz - Kodirov, Khusanhon Munavarkhan ugli; Yuldashev, Shukurullo Nematjon ugli (Educational Research in Universal Sciences, 2023)
The dynamic viscosity values of the oil were determined by monitoring the vibration acceleration at a value higher than 1 kHz. The degree of dependence of vibration acceleration on dynamic viscosity was determined.